A Structural Equation Modeling Approach to Exploring the Role of Emotional Factors in Student Anxiety amid Public Demonstrations - Sisti Nadia Amalia; Hafizha Zahra; Zul Amry (JURNAL ASIMILASI PENDIDIKAN, 2026)
This study investigates the role of emotional factors in student anxiety amid public demonstrations using a Structural Equation Modeling (SEM) approach. The study focuses on emotional intensity and emotional regulation as key psychological constructs within a socio-political context. The sample consisted of approximately 202 students from the Mathematics Department of the Faculty of Mathematics and Natural Sciences at Universitas Negeri Medan, selected through stratified random sampling. Data were collected using standardized instruments, including the Affect Intensity Measure (AIM), the Emotion Regulation Questionnaire (ERQ), and an adapted student anxiety scale measured on a five-point Likert scale. The SEM analysis indicates that the proposed model achieved an acceptable level of fit based on established goodness-of-fit criteria. However, the findings reveal that environmental stressors related to public demonstrations, emotional intensity, and emotional regulation do not have a significant direct effect on student anxiety. These results suggest the presence of adaptive psychological mechanisms, such as resilience and desensitization, among students in response to recurring socio-political disturbances. This study highlights the importance of considering contextual and psychological complexity when modeling student anxiety using SEM.